System security enhancement using hybrid HUA‐GPC approach under transmission line(s) and/or generator(s) outage conditions. (29th October 2021) - Alluri, Amarendra; Lanka, Ravi Srinivas; Rao, Rayapudi Sreenivasa
Abstract: In this manuscript, a hybrid HUA‐GPC strategy with unified power flow controller (UPFC) is proposed to enhance that security of power system under the condition of transmission and/or generator failure. The proposed hybrid strategy is joint implementation of Human urbanization algorithm (HUA) and Giza Pyramids Construction (GPC) and commonly named as HUA‐GPC approach. GPC approach is utilized to develop that search behavior of HUA. The main aim of the proposal is the operation and control of electrical system is to satisfy the demand continuously in the absence of failures. A new severity function is created with transmission line loads and bus voltage magnitude deviations. The proposed function and generation fuel cost are evaluated in contingency conditions of transmission line (s) and/or generator (s). System safety in contingency conditions is evaluated with optimal power flow issue. To improve system safety in contingency conditions in the presence of UPFC, it is essential to recognize an optimal position to install this device. To recognize an optimal UPFC position, in this proposal, a HUA‐GPC technique depending on line overload sensitivity index (LOSI) is evolved. The LOSI is assessed for every transmission lines in contingencies. An energy injection model based on UPFC voltage source, incorporation process and optimal location recognition approach depending on line overload sensitivity indices is proposed. The constraints are the constraints of equality and inequality. The proposed approach is then performed on the MATLAB/Simulink work platform and the efficiency is compared with existing strategies. The quality of the solution for the proposed system is analyzed in terms of best aptitude, worst aptitude, mean aptitude, SD, coefficient of variation and the error of best is 1110936.01, 1097382.12, 1107656.56, 1051.98, 0.075, and 0.82.